LO42: Is point-of-care ultrasound a reliable predictor of outcome during atraumatic, non-shockable cardiac arrest? A systematic review and meta-analysis. (May 2019) - Lalande, E.; Burwash-Brennan, T.; Burns, K.; Atkinson, P.; Lambert, M.; Jarman, B.; Lamprecht, H.; Banerjee, A.; Woo, M.
Abstract : Introduction : Point-of-Care Ultrasound (PoCUS) is being increasingly utilized during cardiac arrests for prognosis. Following the publication of recent studies, the goal of this study was to systematically review and analyze the literature to evaluate the accuracy of PoCUS in predicting return of spontaneous circulation (ROSC), survival to hospital admission (SHA), and survival to hospital discharge (SHD) in adult patients with non-traumatic, non- shockable out- of-hospital or emergency department cardiac arrest.Methods : A systematic review and meta-analysis was completed. A search of Medline, EMBASE, Cochrane, CINAHL, ClinicalTrials.gov and the World Health Organization Registry was completed from 1974 until August 24th 2018. Adult randomized controlled trials and observational studies were included. The QUADAS-2 tool was applied by two independent reviewers. Data analysis was completed according to PRISMA guidelines and with a random effects model for the meta-analysis. Heterogeneity was assessed using I-squared statistics.Results : Ten studies (1, 485 participants) were included. Cardiac activity on PoCUS had a pooled sensitivity of 59.9% (95% confidence interval 36.5%-79.4%) and specificity of 91.5% (80.8%-96.5%) for ROSC; 74.7% (58.3%-86.2%) and 80.5% (71.7%-87.4%) for SHA; and 69.4% (45.5%-86.0%) and 74.6% (59.8%-85.3%) for SHD. The sensitivity of cardiac activity on PoCUS for predicting ROSC was 24.7%(6.8%-59.4%) in the asystole subgroup compared with 77% (59.4%-88.5%) within the PEA subgroup. Cardiac activity on PoCUS, compared to an absence had an odd ratio of 15.9 (5.9-42.5) for ROSC, 9.8 (4.9-19.4) for SHA and 5.7 (2.1-15.6) for SHD. Positive likelihood ratio (LR) was 6.65 (3.16-14.0) and negative LR was 0.27 (0.12-0.61) for ROSC.Conclusion : Cardiac activity on PoCUS was associated with improved odds for ROSC, SHA, and SHD among adults with non-traumatic asystole and PEA. We report lower sensitivity and higher negative likelihood ratio, but with greater heterogeneity compared to previous systematic reviews. PoCUS may provide valuable information in the management of non-traumatic PEA or asystole, but should not be viewed as the sole predictor in determining outcomes in these patients.